Growth and Yield Stability of Sweet Potato Clones across Four Locations in East Nusa Tenggara - Mau, Yosep Seran; Ndiwa, Antonius S. S.; Arsa, I.G.B. Adwita; Oematan, Shirly S. (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2013)
A number of promising sweet potato clones from East Nusa Tenggara and a checked cultivar were evaluated in several locations for the following objectives: 1) to elucidate genotype by environment effect on growth and yield of the sweet potato clones, and 2) to determine growth and yield stability of the clones across diverse locations in East Nusa Tenggara province. The study was carried out in four locations and was laid out in a Randomized Block Design consisting of 10 sweet potato genotypes as treatments and two replicates. Obtained data were subjected to combined analysis of variance to determine GxE interaction, followed by stability analysis based on joint regression model of Eberhart and Russell. Research results revealed that genotypes, locations and genotype by location interaction posed significant effect on the observed variables. Most of the evaluated clones were unstable for vegetative growth characters but were stable for tuber yield and yield components. The local clone LB-01 produced the highest mean tuber yield over all locations, averaging at 4.15 kg.plant-1 ( 46.11 t.ha-1). Two local clones, i.e. ON-06 and LB-01, and the check cultivar Kidal were the most stable clones for tuber yield and yield components across diverse environments. Keywords: growth, yield, stability, sweet potato, location